Role of internet of things for health-care monitoring during COVID-19 pandemic - Abid Haleem; Mohd Javaid; Raju Vaishya; Abhishek Vaish (Apollo Medicine)
Internet of Things (IoT) is already being implemented in the medical field to improve the treatment outcome. This technology also plays a significant role during the COVID-19 pandemic for the betterment of the infected patient. With such high levels of infection of the SARS-CoV-2 virus, organisations want to automate hospital facilities, so there is a need for this technology for improving hospital management and patient care system. A proper application & implementation of these technologies may reduce the chances of mistakes and provides effective control during the entire treatment process of COVID-19 patients. This short review identifies and discusses significant roles of IoT in taking up major healthcare challenges during the COVID-19 pandemic. IoT helps identify the symptoms and provides a rapid treatment process with the help of internet-connected devices and networks. It automatically helps to manage the medical staff to maintain quality supervision. There are an adequate flow and better safety of the patient in the internet-connected hospital. It helps provides real-time information to create transparency in the treatment. In the future, this technology can predict the upcoming situation and make appropriate forecasting regarding this virus.